Analysis of Judges' Considerations in Considering and Imposing a Niet Ontvankelijke Verklaard (N.O) Decision at the Sleman District Court - Susilo, Joko; Gunawan, Ade (LEGAL BRIEF, 2024)
This research explores lawsuits containing formal defects from 2022-2023 which resulted in a lawsuit being declared inadmissible or Niet Onvankelijkverklaard by the judge. The focus is to examine what the judge considers so that the judge in his decision makes a decision containing the ruling that the lawsuit is declared inadmissible or Niet Onvankelijkverklaard. This research applies the normative-empirical method using a qualitative descriptive approach, namely the research process by seeking information by going to the field by visiting the Sleman District Court. The research data sources are primary and secondary data sources, primary data sources are through laws and information obtained in the field while secondary data sources are literature studies such as journals, books and encyclopedias. The results of this study are from the 2022-2023 decision data, it was found that most of the decisions were declared unacceptable due to obscuur libel and the factors of unacceptable decisions other than obscuur libel were also suspected of other factors such as lack of parties, premature lawsuits and unclear legal standing